Existence of equilibrium solution for a non- cooperative game with fuzzy goals and parameters - Kacher, F; Larbani, Moussa (Elsevier, 2008)
In this paper we introduce a concept of equilibrium for a non- cooperative game with fuzzy goals involving fuzzy parameters. This equilibrium is based on Zimmermann's approach for solving linear multiobjective problems with fuzzy goals and the concept of N-S equilibrium introduced by Zhukovskii for a non- coprative game with payoffs involving unknown parameters in the case of complete ingnorance of their behavior. We also provide a theorem of existance of this equilibrium based on the Fan ineqality.